Territorial and occupancy behavior of black sea bass on oyster aquaculture gear and boulder habitat - Armbruster, Adam D.; Mercaldo-Allen, Renee; Rose, Julie M.; Seda, Kristen; Clark, Paul; Phillips, Gillian; Redman, Dylan; Conroy, Christian W. (Frontiers in Marine Science, 2024)
Observations of fish behavior can provide insights into habitat preferences and use. Black sea bass, Centropristis striata, are a territorial temperate reef finfish species known for their high commercial and recreational value and association with structured habitat. We used underwater action cameras to record video of black sea bass to assess territorial (agonistic, ambush, displacement) and occupancy (station-keeping) behaviors on shelf and bag style oyster aquaculture cages at a shellfish farm, and on boulders at a natural rock reef near Milford, Connecticut in Long Island Sound, Northwest Atlantic. Black sea bass at a variety of life stages were highly associated with cages, including young-of-the-year, and age 1+ fish. The high abundance of black sea bass observed on cages relative to boulders suggests this species has an affinity for the vertical structure created by aquaculture gear. When behaviors were normalized to the total fish sightings, black sea bass showed no significant difference in frequency of behaviors between habitats, indicating that per-fish rates of behavior were similar on cages and boulders. Demonstration of territorial and occupancy behaviors by black sea bass on, and around cages suggests that aquaculture gear provides structured habitat and ecosystem services for this species similar to natural reefs.These results suggest that essential fish habitat descriptions of manmade structures used by black sea bass could be broadened to include aquaculture gear. Our study provides novel information on behavioral interactions of black sea bass with oyster cages that may support aquaculture permitting and consultation processes.